明清古典文学在北欧的译介与传播——兼论汉学诠释中哲学精神对传译策略和风格的影响 - 高源; Gao Yuan (厦门大学学报（哲学社会科学版）编辑部, 2019)
高源，中山大学哲学系（珠海）副研究员，芬兰科学院暨芬兰赫尔辛基大学宗教学院研究员，芬兰赫尔辛基大学哲学与宗教学博士(Ph.D.=Th.D.)。 【中文摘要】在20世纪海外汉学的译介与传播中，明清文学典籍占据了相当大的比重并在欧美世界产生了较深远的影响。然而，关于斯堪的纳维亚世界的传译情况却较少有中文文献进行系统梳理。究其缘由，北欧五国各自独立的语言系统及其根植于奥古斯丁-路德宗教传统的社会生活形态与汉语语境迥然不同。面对深刻的文化隔阂，如何将中国古典文学著作转换为当地喜闻乐见的 文本形式并进行有效传播,则是一个重要的议题。切入斯堪的纳维亚国家（芬兰、瑞典、丹麦、挪 威、冰岛）语境来考察明清古典文学的译介形态、发展脉络、基本特质及其传播模式,进而透过文本形式的分析来深入探讨其背后不同哲学思维与信仰价值的互动，将有助于了解中国古典文学在北欧的译介规律和传播动态。 【Abstract】The translation of Ming-Qing literature played a significant role in the overseas introduction of Sinology in the last century- However，there is a dearth of systematic study in the Chinese language of the circulation of these materials in the Scandinavian academic world. A possible reason may be that the languages of the five Nordic countries，which were rooted in the Augustinian-Lutheran tradition，have a large gap with the Chinese context.In confronting this cultural gap，it is important to consider how the terminology of classical works was imported into indigenous Nordic texts so as to facilitate their reception by local readers. This article provides an in-depth examination of the introduction of the Ming-Qing classical literature to five countries，namely，Finland，Sweden，Denmark，Norway and Iceland，with a focus on translation status， development outlines，general features and circulation models. Through a systematic analysis of the text，it explores the interaction of the two traditions between the distinct philosophical values and beliefs，with a view to better understanding the spread of classical Chinese literature to the Nordic countries. 教育部人文社会科学研究基金项目“海上丝绸之路：儒家经典首次西传中的拉丁文译本研究” (19YJC720012);芬兰科学院国家重大项目 “The Impact of Religious Values on Chinese Social Life” ( FIN-314707)